How Do Shipworms Eat Wood? Screening Shipworm Gill Symbiont Genomes for Lignin-Modifying Enzymes - Stravoravdis, Stefanos; Shipway, J. Reuben; Goodell, Barry (Frontiers in Microbiology, 2021)
Shipworms are ecologically and economically important mollusks that feed on woody materials in marine environments. Previous research has shown that the site of wood digestion, the cecum, is virtually sterile and lacks resident gut microbiota; however, within the gills, shipworms possess endosymbiotic bacteria that contribute to wood digestion. Previous studies have overlooked how shipworms and their gill symbionts process lignin, a tough, aromatic polymer blocking access to the holocellulose components of wood. Enzymatic or non-enzymatic modification and depolymerization of lignin has been shown to be required in other wood-degrading biological systems as a precursor to cellulose deconstruction. We investigated the genomes of five gill bacterial symbionts obtained from the Joint Genome Institute Integrated Microbial Genomes and Microbiomes Expert Review for the production of lignin-modifying enzymes, or ligninases. The genomes were searched for putative ligninases using the Joint Genome Institute’s Function Profile tool and blastp analyses. The resulting proteins were then modeled using SWISS-MODEL. Although each bacterial genome possessed at least four predicted ligninases, the percent identities and protein models were of low quality and likely unreliable. Prior research suggests little ability of shipworms themselves to modify lignin at the chemical/molecular level and our results also suggest that bacterial gill-symbiont enzymes are unlikely to play a role in lignin modification during lignocellulose digestion in the shipworm gut. This suggests that our understanding of how these keystone organisms digest and process lignocellulose is incomplete, and further research into non-enzymatic mechanisms for lignin modification are required.